Hematologi dan Histopatologi Insang Ikan Lele Hasil Budidaya Pembudidaya Lokal di Noekele, Kabupaten Kupang Timur - Shobikhuliatul Jannah Juanda; Ion Tarsardo Sianturi; Yusuf Kamlasi; Muhammad Fajar Panuntun (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
The aim of this study was to determine the haematological and histopathological of the Catfish gills cultured in Noekele, East Kupang, East Nusa Tenggara. The fish samples used were catfish taken randomly as many as 80 individuals from the rearing pond owned by local farmers in Noekele, then taken to the laboratory for measurement of length and weight, morphological abnormalities observation, preparation of fish blood smears and collection of gills for histological preparation. The observation of morphological abnormalities showed body lesion (90%), one ventral fins (31.3%), one pectoral fins (28.8%), dull and pale body colors (100%). Erythrocyte cell damage on haematological observation on blood smear were tear drop shaped, fusion, lacerated membrane, nuclear extrusion, blebbed nuclei, sperocytes (deformed cells), lysis and shrinking erythrocytes. Based on histopathological analysis, gill’s damage were secondary lamella edema, primary lamella vacuoles, secondary lamella necrosis, epithelium lifting, secondary lamella fusion. Loss of lamella structure, hyperplasia and presence of parasites.